A study of sewage sludge Co-gasification with waste shiitake substrate. (15th November 2022) - Chen, Guan-Bang; Wu, Fang-Hsien; Lin, Sheng-Pin; Hsu, Yun-Ting; Lin, Ta-Hui
Abstract: This study investigated the co-gasification of sewage sludge and waste shiitake substrates. The fuel properties were analyzed, and a lab-scaled bubbling fluidized-bed gasifier was used to identify the effects of the equivalence ratio (ER), gasification temperature, and blending ratio (BR) on the gas yield, lower heating value (LHV), cold gas efficiency (CGE), and carbon conversion efficiency (CCE). The results showed that a higher ER promoted the gasification of sewage sludge, while it was not conducive to gasification of shiitake substrates due to the oxidation reaction. A high gasification temperature increased the gas yield for both feedstocks. For the blended fuels, BR = 25% exhibited better gasification performance, with a maximum LHV at ER = 0.1. The effect of the BR decreased with ER, and the gasification performance was close to that of pure sludge at ER = 0.25. The CGE decreased with ER at BR = 0% and 25%, whereas it slightly increased with ER at BR = 75% and 100%. In addition, CCE increased with ER at the different blends, whereas it exhibited marginal variations for pure shiitake. Finally, an ASPEN Plus model was developed and the co-gasification characteristics of sewage sludge and waste shiitake substrates were successfully predicted. Graphical abstract: Image 1 Highlights: Co-gasification of sewage sludge (SS) and waste shiitake substrate were studied. SS had the best syngas yield at ER = 0.25, while it was at ER = 0.1 for shiitake. BR 25% blended fuel had better gasification performance, especially at ER = 0.1. ASPEN Plus simulation with kinetic model and tar reactions was performed. The kinetic model greatly reduced the error by 65–94% for the syngas composition.